Protocol for cell-type-specific tissue reconstruction in the murine lung fibrogenic microenvironment - Koichi Hasegawa; Ryo Miyata; Toshi Menju; Toyohiro Hirai; Hiroshi Date; Atsuyasu Sato (STAR Protocols, 2023)
Summary: Pulmonary fibrosis is a process characterized by epithelial injury and fibroblast activation. It is also well recognized as a predisposition to lung cancer. Here, we present a protocol to establish an in vivo model to evaluate the dynamics of alveolar epithelial type 2 cells and lung cancer cells in the context of the lung fibrogenic microenvironment. Utilizing the cell transfer technique, we detail a basis for therapeutic approaches in pulmonary fibrosis and tools for precision medicine against lung cancer.For complete details on the use and execution of this protocol, please refer to Miyata et al. (2022).1 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.